Programa de Coleta Seletiva Solidária em universidade sob o olhar da Ciência, Tecnologia e Sociedade - Flamini, Silvia Helena (2021)
In Brazil, experiences have been developed on solid waste management in federal institutions of higher education, since they are considered major generators of this waste and must comply with Federal Decree No. 5.940/06, which institutes the separation and disposal of their recyclable solid waste to cooperatives or associations of waste pickers. At the Federal University of São Carlos (UFSCar) there is the Permanent Program for Management and Shared Management of Solid Waste and Selective Solidarity Collection at UFSCar (called the Program) in São Carlos, Sorocaba, Araras and Lagoa do Sino campuses. In São Carlos, there is the partnership with COOPERVIDA, which is the municipal work cooperative of waste pickers, and the extension project “Solidarity Selective Collection at UFSCar: Environmental Management and Education”, which is linked with this Program, comprising two fronts of performance: one directed to management with the monitoring and follow-up of COOPERVIDA's equipment and work and another specific to Environmental Education. The general objective of this research is to identify favoring aspects that expand the socio-environmental, political and cognitive potential related to solidary selective collection under the prism of the field of Science, Technology and Society and the view of Solidarity Technoscience, in addition to specifically proposing sociotechnical artifacts fundamental for the further elaboration of indicators, by the university management, as instruments of analysis and monitoring of the solidary selective collection at UFSCar. As a methodological strategy, a case study was carried out on the institution's headquarters campus, with the development of exploratory-descriptive field research of the quanti-qualitative type, applying a network of actions that consisted of consulting official documents and socio-environmental legislation; investigate the current institutional political status; analyze the infrastructure of the Selective Solidarity Collection Program; collect data and perceptions of social groups directly related to actions of solidary selective collection; consult academic-scientific literature on sustainability indicators in the management and management of recyclable solid waste; and consult the available literature on Solidarity Technoscience. According to the results presented and discussed, UFSCar's solidary selective collection ends up in a network of actions composed of social groups that need to actively participate in decision-making, as a rapprochement of the university to solidary selective collection and waste pickers can reduce or mitigate problems and conflicts on campus, maximizing the resulting social, political and environmental potential. In this sense, an institutional commitment is needed to support the actions of solidary selective collection with regard to political and economic aspects, ensuring compliance with legal instruments, investment on financial and human resources. In addition, solidary selective collection can also promote actions in the field of knowledge production, human (trans)formation and technoscientific innovation based on a cognitive proposal that brings the collectivity, solidarity and belonging of social groups related to its actions, building knowledge that serve as a cognitive alternative that proposes different values, given the current paradigm of technoscientific production characterized by intellectual appropriation and social exclusion. The solidary selective collection adequate to the Solidarity Technoscience molds is the basis for the construction of a cognitive and political platform to be used as a means for cultural, institutional and scientific-technological change, as it carries the potential of (re)modeling conducts and values, as well as forming critical positions regarding the conception of the socio-environmental context, thus becoming synonymous with the provision of quality public services.